Optimasi Formulasi Cleansing Balm Minyak Biji Tomat (Solanum lycopersicum) dengan Simplex Lattice Design: Karakteristik Fisik dan Efek Anti-Aging - Suryani , Arman; Cahyaningsih , Tri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
This study aims to optimize the formulation of tomato (Solanum lycopersicum) seed oil-based cleansing balm with a Simplex Lattice Design (SLD) approach and evaluate its physical characteristics for facial cleansing and potential anti-aging effects. The research method used was formulation with the main component variables of shea butter, beeswax, caprylic/capric triglycerides, and tween 20, which were analyzed using SLD to obtain the optimal combination. The optimization results showed that the formulation with concentrations of shea butter (4.97996 %), beeswax (1.88189 %), caprylic/capric triglycerides (42.1382 %), and tween 20 (1 %) provided a good quality preparation with a semi-solid texture, typical beeswax aroma, and bone white color. The physical characteristics of the product, such as melting temperature stabilized at 38.67 °C ± 0.58, spreadability of 5.43 cm ± 0.12, and pH of 5.03 ± 0.06, showed that the product was safe and ideal for the skin. The product stability test for seven days of storage showed no significant changes in melting temperature and spreadability, although there was a slight increase in pH. In addition, the product showed good antioxidant activity with 46.51% free radical inhibition and an IC50 value of 21.46 ppm, indicating potential protection against oxidative stress-induced skin damage. In conclusion, the tomato seed oil cleansing balm optimized through SLD has stable, safe, and effective performance as a skincare product with anti-aging benefits.